The impact of smart cities on entrepreneurial activity: Evidence from a quasi-natural experiment in China. (March 2023) - Li, Chengming; Zhang, Xinyi; Dong, Xiaoqi; Yan, Qiangming; Zeng, Liangen; Wang, Zeyu
Abstract: Over the past decade, Smart Cities initiatives have attracted a great deal of global attention from governments and scholars. However, less attention has been given to the impact of Smart Cities construction on local entrepreneurial activity. This paper assesses the impact of Smart Cities construction on urban entrepreneurial activity using the difference-in-difference (DID) model based on panel data from 265 prefecture-level cities in China from 2002 to 2019. The empirical results show that Smart Cities policies significantly enhance urban entrepreneurial activity. After the parallel trend and placebo test, the estimation results based on the PSM-DID (Propensity Score Matching-Difference in Difference) method are robust and consistent with the baseline regression results. The mechanism analyses indicate that the possible channels for Smart Cities policies to exert a positive impact on urban entrepreneurial activity are improving the city's ability to attract investment and enhancing technological innovation. Furthermore, Smart Cities policies have a more significant incentive effect on entrepreneurial activity in eastern regions, larger-scale cities, and cities with higher levels of service informatization and a larger scale of government financial expenditure. This paper contributes to the policy effects of Smart Cities pilots and the factors influencing entrepreneurial activity. This paper has important implications for enhancing entrepreneurial market dynamics and promoting urban transformation programs in developing countries to empower a sustained wave of urban entrepreneurship. Highlights: Smart Cities policies significantly enhance urban entrepreneurial activity. Smart Cities policies improve urban entrepreneurial activity by attracting investment and enhancing technological innovation. The impact of Smart Cities policies on entrepreneurial activity is heterogeneous.